1996
DOI: 10.1007/bf01411116
|View full text |Cite
|
Sign up to set email alerts
|

Management of symptomatic carotid stenoses with coincidental intracranial aneurysms

Abstract: There are at present strong indications for surgery in patients suffering from symptomatic extracranial carotid stenoses of > 70%. Surgery of coincidental aneurysms is a still debated problem, but there is general agreement that it is indicated in selected cases according to the patient's life-expectancy and size and site of the aneurysm. The coexistence of these two lesions raises a decision-making problem. We reviewed 389 endarterectomies and found 12 intracranial berry aneurysms in 10 (2.6%) patients. All t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 32 publications
0
25
0
Order By: Relevance
“…Sex-specific prevalences could be retrieved from our study and 2 studies from the literature review. 2,5 In these three studies, women had a higher risk of aneurysms than men (relative risk 1.6; 95% CI 1.1 to 2.3).…”
Section: Metaanalysismentioning
confidence: 92%
See 2 more Smart Citations
“…Sex-specific prevalences could be retrieved from our study and 2 studies from the literature review. 2,5 In these three studies, women had a higher risk of aneurysms than men (relative risk 1.6; 95% CI 1.1 to 2.3).…”
Section: Metaanalysismentioning
confidence: 92%
“…Mean ages ranged form 62 to 72 years old. The populations were North American 2,6 or European (Italy, 3,5 Great Britain 2,4 ). A total of 147 aneurysms was found in 136 patients.…”
Section: Metaanalysismentioning
confidence: 99%
See 1 more Smart Citation
“…During an average five-year follow-up, only one patient had SAH six days after CE. Although some reports suggest no increased risk of rupture in asymptomatic aneurysms after carotid revascularization 2,4 , several studies have concluded that the treatment of either condition may provoke events related to the other lesion, which include subarachnoid hemorrhage after revascularization of carotid artery stenosis and perioperative stroke related to carotid artery stenosis after aneurysmal treatment 1,5 . The sequence of treatment and the number of sessions are the critical issues that should be addressed.…”
Section: Discussionmentioning
confidence: 99%
“…endarterectomy (6,14) performing both the procedures in the same sitting (17) and performing carotid angioplasty/ endarterectomy without repairing the intracranial aneurysm (7,9,13) However there are no reports of coiling of aneurysm in patient with significant stenosis without treating the parent vessel carotid origin stenosis. We hereby report three cases of cerebral aneurysm with ipsilateral cervical carotid stenosis in whom successful embolization of aneurysm was done safely without carotid revascularization before or at the time of the embolization.…”
Section: Gupta V Et Al: Coil Embolization Of Intracranial Aneurysms mentioning
confidence: 99%